Protective Effects of Carotenoid-Loaded Nanostructured Lipid Carriers Against Ochratoxin-A-Induced Cytotoxicity - Nicola Pinna; Pilar Vila-Donat; Denisia Pașca; Francesca Blasi; Aurélie Schoubben; Lara Manyes (Foods)
Ochratoxin A (OTA) is a mycotoxin produced by Aspergillus ochraceous and various Penicillium species, which are known for contaminating agricultural products and posing significant health risks, which include immunotoxicity. This study aims to evaluate the potential of nanostructured lipid carriers (NLCs) loaded with a carotenoid-enriched extract from pumpkin peel (Cucurbita maxima L.) in mitigating the toxic effects of OTA. To address the poor bioavailability and instability of carotenoids, nanoencapsulation techniques were employed to enhance their delivery and efficacy. NLCs were formulated using hydrogenated sunflower oil, pumpkin oil, and soy lecithin using hot high-pressure homogenization. The in vitro study involved co-digesting OTA-contaminated bread with an NLC formulation and assessing the impact of the encapsulated carotenoid on OTA bioaccessibility, bioavailability, and cellular toxicity using Caco-2 and Jurkat T cells. Even though no significant influence was observed on the bioaccessibility and bioavailability of OTA, carotenoid-loaded NLCs exhibited cytoprotective effects by improving cell viability and mitigating OTA-induced toxicity in both Caco-2 and Jurkat T cells. Particularly, the flow cytometry analysis highlighted the ability of carotenoids to mitigate OTA-induced cellular damage by decreasing ROS production and limiting mitochondrial mass changes. The study suggests that the encapsulation of carotenoids in NLCs represents a promising strategy to enhance their protective effects against OTA toxicity, potentially offering a novel approach to food safety and public health protection. The study underscores the potential of nanotechnology in improving the bioavailability and efficacy of natural antioxidants to mitigate mycotoxin-induced damage.